THE EFFECT OF LEADERSHIP ETHICS AND ORGANIZATIONAL CULTURE - Efendi Rahmanto (Universitas 45 Surabaya, 2023)
This study aims to determine the influence of ethical leadership, organizational culture, commitment to organizational performance. It also examines the mediating effect of commitment in relationships between ethical leadership and organizational performance, and between organizational culture and organizational performance. This research uses primary data by distributing questionnaires. The research method is a method quantitative And technique analysis data Which used is SEM with use program SmartPLS 3.0. Sample study as much 98 respondent And study done in industry shipping, Patimban, Subang Regency. The results of the study show that ethical leadership, organizational culture, and commitment proved to have a significant positive effect on organizational performance. Besides That, proven significant positive between culture organization to commitment And influence organizational culture on organizational performance through commitment as a mediating variable. However, the effect of ethical leadership on commitment and the effect on leadership variables ethics to performance organization through commitment as variable mediation, proven No significant.